Alternative Perspectives: How Chinese Medicine Understands Hypercholesterolemia. (5th July 2010) - O'Brien, Kylie A.
Abstract : Treatment of cardiovascular disease, albeit under the auspices of other clinical descriptors to those described in western biomedicine, has a long history in China. Chinese Medicine (CM) is guided by unique philosophical underpinnings and theories. There are differences in how the heart is conceptualised traditionally in CM compared to biomedicine. This paper focusses on how hypercholesterolemia is understood from within the Chinese medical paradigm, including its aetiology, pathogenesis, and treatment. A brief overview of the key characteristics and theories of CM is given to provide context. Modern science has demonstrated that many Chinese herbs have cholesterol-lowering properties. Examples of research into individual herbs and medicinal formulae, combinations of herbs are presented. At a more sophisticated level, some researchers are challenging some of the very assumptions upon which CM is based, including applicability of CM theory to modern clinical entities such as hypercholesterolemia, and are seeking intersections of knowledge between CM and biomedicine that may extend CM theory.